2018
DOI: 10.3390/genes9040225
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Guided Analysis of Clostridium ultunense and Comparative Genomics Reveal Different Strategies for Acetate Oxidation and Energy Conservation in Syntrophic Acetate-Oxidising Bacteria

Abstract: Syntrophic acetate oxidation operates close to the thermodynamic equilibrium and very little is known about the participating organisms and their metabolism. Clostridium ultunense is one of the most abundant syntrophic acetate-oxidising bacteria (SAOB) that are found in engineered biogas processes operating with high ammonia concentrations. It has been proven to oxidise acetate in cooperation with hydrogenotrophic methanogens. There is evidence that the Wood-Ljungdahl (WL) pathway plays an important role in ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 94 publications
3
39
0
Order By: Relevance
“…D). This scenario is very similar to the energy conservation mechanism utilized by the syntrophic acetate oxidizer Clostridium ultunense (Manzoor et al ., ). RBG‐16‐55‐9 genomes also encode a high‐affinity acetate transporter belonging to the sodium: solute symporter family (TC: 2.A.21, pfam 00474) similar to the one identified in the acetate oxidizer Syntrophoaceticus schinkii (Manzoor et al ., ) (Fig.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…D). This scenario is very similar to the energy conservation mechanism utilized by the syntrophic acetate oxidizer Clostridium ultunense (Manzoor et al ., ). RBG‐16‐55‐9 genomes also encode a high‐affinity acetate transporter belonging to the sodium: solute symporter family (TC: 2.A.21, pfam 00474) similar to the one identified in the acetate oxidizer Syntrophoaceticus schinkii (Manzoor et al ., ) (Fig.…”
Section: Resultsmentioning
confidence: 85%
“…(ii) An ion gradient‐driven phosphorylation, as the net ATP production by SLP during WL pathway is zero. (iii) A high affinity acetate transporter, as SAO bacteria are present in environments where acetoclastic methanogens are also prevalent and competition for acetate as a carbon source is expected (Manzoor et al ., ; ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The energy conservation strategies of Pelotomaculum and Syntrophobacter clearly differ, where Syntrophobacter seemed to have a more intricate energy conservation mechanism. A recent study has also reported contrasting energy conservation mechanisms among syntrophic acetate and aromatic compound oxidizers (Nobu et al ., ; Manzoor et al ., ), suggesting diversity in energy metabolism across syntrophic organisms.…”
Section: Resultsmentioning
confidence: 99%